Ex-situ conservation and management of dipterocarps genetic resources through seedlings collections and nursery establishment - HENTI HENDALASTUTI RACHMAT; Rizki Ary Fambayun; KUSUMADEWI SRI YULITA; ARIDA SUSILOWATI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Rachmat HH, Fambayun RA, Yulita KS, Susilowati A. 2020. Ex-situ conservation and management of dipterocarps genetic resources through seedlings collections and nursery establishment. Biodiversitas 21: 556-563. Dipterocarpaceae is a pantropical tree family that spread throughout Asia, including Indonesia. Dipterocarps species are highly valued for their timber. However, their existence is threatened due to illegal logging, forest degradation, and land conversion, result in population reduction in their natural habitat. Conservation nursery is one of germplasm conservation concepts that contain a living collection of endangered, commercially valuable, and multi-purpose tree species. Related to this nursery concept, Forest Research and Development Agency (FORDA) collaborated with Komatsu established a KoFCo nursery (Komatsu- FORDA Conservation Nursery). The establishment of this nursery was by field collection of dipterocarps species as targeted species, followed by sowing and acclimatization for seed and wildings, vegetative propagation using the KOFFCO cutting system, and nursing (watering, weeding, fertilizing, and soil change). At present, the KoFCo nursery has ca. 13,000 individuals of nine genera of dipterocarps seedlings originated from fifteen provinces in Indonesia. Of these, 76 species (68%) are categorized as threatened based on the IUCN red-list category and criteria. Hence, more than 60% of these threatened species were conserved and well-managed through KoFCo nursery. Seedlings collection and KoFCo nursery, therefore, play a vital role and support in ex-situ conservation effort and management of dipterocarps genetic resources.